2000
DOI: 10.1034/j.1600-0641.2000.033004564.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral ciprofloxacin after a short course of intravenous ciprofloxacin in the treatment of spontaneous bacterial peritonitis: results of a multicenter, randomized study

Abstract: Oral ciprofloxacin after a short course of i.v. ciprofloxacin is effective in the treatment of spontaneous bacterial peritonitis. This regimen can be applied to all patients admitted to the hospital with this complication, and could be an alternative to treating these patients as outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 0 publications
0
43
0
3
Order By: Relevance
“…Fortunately, these organisms retain their sensitivity to cefotaxime [62,63] , but this emphasizes the concept that patients who develop SBP on quinolone prophylaxis should not receive these drugs for treatment but instead undergo treatment with a third-generation cephalosporin (i.e. cefotaxime) [48,51,55] .…”
Section: Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, these organisms retain their sensitivity to cefotaxime [62,63] , but this emphasizes the concept that patients who develop SBP on quinolone prophylaxis should not receive these drugs for treatment but instead undergo treatment with a third-generation cephalosporin (i.e. cefotaxime) [48,51,55] .…”
Section: Prophylaxismentioning
confidence: 99%
“…The treatment of patients with a potentially life-threatening infection using outpatient oral antibiotics is controversial, especially as 50% of patients with SBP have concomitant bacteremia, compliance cannot be assured, and serial examinations and repeat ascitic fl uid analysis are diffi cult [48] . Perhaps an initial course of inpatient intravenous antibiotics for several days followed by outpatient oral therapy once the stability of the patient is assured would be a reasonable option, but is one that still needs further evaluation in future prospective studies [48,55] . Patients suspected to have secondary bacterial peritonitis should additionally be placed on antibiotics with enterococcal and anaerobic coverage [5,44] and undergo laparotomy if a surgical source of infection is confi rmed on radiologic investigation [43] .…”
Section: Diagnosismentioning
confidence: 99%
“…This is a new finding, as immunosuppression has not been investigated as a predictive factor of mortality in previous SBP series. [31][32][33][34] The degree of liver function and renal failure are classical predictive factors of mortality. However, immunosuppression is not an unexpected predictive factor.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies confirmed the safety and efficacy of intravenously administered amoxicillin/clavulanic acid (3-4x1.2 g) in the treatment of SBP [82,83]. In uncomplicated SBP (absence of the followings: ileus, gastrointestinal bleeding, septic shock, HE with grade 2-4 or serum creatinin  3 mg/dL) oral, highly bioavailable quinolones (ofloxacin 2x400 mg, ciprofloxacin 2x500 mg) have been found as effective as the intravenous third-generation cephalosporins [84,85]. However, quinolons are not recommended in patients receiving norfloxacin prophylaxis or in geographic areas with a high prevalence of quinolone-resistant bacteria.…”
Section: Spontaneous Bacterial Peritonitis (Sbp)mentioning
confidence: 94%